Distinct Age-Related Epigenetic Signatures in CD4 and CD8 T Cells - Hu, Bin; Jadhav, Rohit R.; Gustafson, Claire E.; Le Saux, Sabine; Ye, Zhongde; Li, Xuanying; Tian, Lu; Weyand, Cornelia M.; Goronzy, Jörg J. (Frontiers in Immunology, 2020)
Healthy immune aging is in part determined by how well the sizes of naïve T cell compartments are being maintained with advancing age. Throughout adult life, replenishment largely derives from homeostatic proliferation of existing naïve and memory T cell populations, however, CD4 T cells appear to more resilient than CD8 T cells to resist age-associated changes; while the subpopulation composition of CD4 T cells is relatively stable, the CD8 T cell compartment undergoes more drastic changes with loss of naïve CD8 T cells and accumulation of effector T cells. To determine the epigenetic basis for these differences in behaviors, we compared chromatin accessibility maps of CD4 and CD8 T cell subsets in the context of age. The dominant age-associated signatures resembled hallmarks of differentiation, which were more pronounced for CD8 naïve and memory than the corresponding CD4 T cell subsets, suggesting that CD8 T cells are under higher proliferative stress in maintaining homeostasis or are less able to keep cellular quiescence. In parallel, aged CD8 T cells, irrespective of their differentiation state, displayed greater reduced accessibility to genes of basic cell biology function, including genes encoding ribosomal proteins, likely due to the reduced expression of the transcription factors YY1 and NRF1. While it remains to be determined how these epigenetic changes are mechanistically related, chromatin accessibility signatures can be identified that reflect the higher resilience of CD4 T cells to T cell aging.